Latin American art of the 20th century - Lucie-Smith, Edward (New York, N.Y. : Thames and Hudson, 2004)
"Edward Lucie-Smith discusses major subjects and issues: Magic Realism, Expressionism and other concepts shared with Latin American literature; the great muralists Diego Rivera, David Alfaro Siqueiros and Jose Clemente Orozco; the interaction of politics, society and art; the continuing interest in folk art; and the dialogue between avant-garde European and North American movements and "indigenist" thinking in the work of artists such as Wifredo Lam, Matta, Rufino Tamayo and Frida Kahlo. A new final section presents the leading artists of today, some of whose work in the fields of interactive installation, photography and video art reveals a continent embracing the experimental and the new."--BOOK JACKET.
1. Forerunners and independents --2. The first modern movements --3. Mexican muralism --4. Muralism beyond Mexico --5. The exiles --6. Mexico : four women and one man --7. A climate of change --8. Geometric abstraction --9. Informal abstraction --10. Expressionist tendencies --11. Realism, pop art and surrealism --12. The present day.
Includes bibliographical references (pages 216-218) and index.
Keywords: Art, Latin American -- 20th century